2022
DOI: 10.1002/pc.26698
|View full text |Cite
|
Sign up to set email alerts
|

Study on properties of gelatin–silica mineralized wood composite

Abstract: Wood is a natural organic composite material that has abundant sources, is renewable, and exhibits an organized structure. However, the fast-growing poplar tree is loose in texture and has poor physical, mechanical, and flame retardant properties. Inspired by the biomineralization mediated by the natural organic matrix, a biocompatible and mineral-inducible gelatin solution is impregnated into the wood. Subsequently, the sol-gel method is used for the in-situ mineralization of silica in wood pores and cell cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It is expected that sol–gel chemistry will still play a key role in flame retardance in the next years with its great potential being further exploited [ 70 ]. Li et al [ 71 ] applied the sol–gel method to mineralize silica in wood pores and cell cavities and applied silica to prepare mineralized wood composites with flame-retardant properties. The results of CONE analysis showed that the ignition time (TTI) of mineralized wood is 21 s. The peak heat release rate associated with cone calorimetry decreased by 45.8%.…”
Section: Improvement Of Flame Retardancy Of the Wood Surfacementioning
confidence: 99%
“…It is expected that sol–gel chemistry will still play a key role in flame retardance in the next years with its great potential being further exploited [ 70 ]. Li et al [ 71 ] applied the sol–gel method to mineralize silica in wood pores and cell cavities and applied silica to prepare mineralized wood composites with flame-retardant properties. The results of CONE analysis showed that the ignition time (TTI) of mineralized wood is 21 s. The peak heat release rate associated with cone calorimetry decreased by 45.8%.…”
Section: Improvement Of Flame Retardancy Of the Wood Surfacementioning
confidence: 99%
“…[35] Moreover, various physical and chemical treatments are applied to wood by many researchers to extend its applicability in different scenarios. [36,37] The amount of waste wood produced each year is substantial, and it is often not fully utilized. Therefore, there is a need for more advanced and efficient methods of recycling that can extract the maximum value from these waste wood resources.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the surface-modified coating possessed flame-retardant properties. Li et al [ 26 ] impregnated a biocompatible and mineral-inducing gelatin into wood and used the sol-gel technique to mineralize silica in wood pores and cell cavities in situ, resulting in mineralized wood composites with good flame-retardant and mechanical qualities.…”
Section: Introductionmentioning
confidence: 99%